Effects of supplementing late-gestation sow diets with zinc on preweaning mortality of pigs under commercial rearing conditions. Issue 2 (29th January 2020) - Holen, Julia P; Urriola, Pedro E; Schwartz, Mark; Jang, Jae-Cheol; Shurson, Gerald C; Johnston, Lee J
Abstract: The objective of this experiment was to determine preweaning survival of pigs when sows were supplemented with 3 dietary levels of zinc (Zn) in late gestation. Gilts and sows ( n = 339) were assigned to 1 of 3 dietary treatments based on parity. Dietary treatments were 1) Control—sows fed a corn–soybean meal-based diet containing 125 ppm total supplemental Zn supplied by ZnSO4 (75 ppm Zn) and AvailaZn (50 ppm Zn, CON); 2) Intermediate—as Control + 240 ppm supplemental Zn as ZnSO4 (INT); and 3) High—as Control + 470 ppm supplemental Zn as ZnSO4 (HI). Final supplemental Zn concentrations of the 3 dietary treatments were 1) CON—125 ppm; 2) INT—365 ppm; and 3) HI—595 ppm. Sows received dietary treatments from about day 85 of gestation until farrowing. Individual piglet birth weights were recorded within 12 h of parturition. Instances of piglet mortality were recorded daily. The statistical model considered fixed effects of treatment and random effects of parity. Piglets from sows fed the INT diet had heavier ( P < 0.05) birth weights than those fed CON (1.42 vs. 1.38 kg, respectively), while offspring from sows fed HI tended to have heavier ( P < 0.10) birth weights (1.40 kg) than pigs from INT sows. Furthermore, incidence of low birth weight pigs was less ( P < 0.05) for sows consuming INT compared with sows fed CON and HI. Despite differences in birth weight, there were no differences ( P > 0.05) in total pigs born, born alive, or weaned, nor differences in individual piglet gain or weaning weight across treatments. Mortality of low birth weight pigs was lowest ( P < 0.05) for offspring from sows fed HI (28.1%) compared with offspring from sows fed INT (36.1%) and CON (38.3%). Similarly, overall piglet mortality tended to decrease ( P < 0.10) as dietary Zn content increased (CON: 15.0%, INT: 13.2%, and HI: 12.2%). A subset of pigs ( n = 420, n = 140/treatment) were selected at weaning to evaluate effects of dietary treatment on postweaning performance. There were no significant effects of sow Zn supplementation on final body weight, days to market, or carcass characteristics of market pigs. Overall, effects of supplemental dietary Zn at 365 and 595 ppm in late gestation improved preweaning survival of low birth weight piglets and reduced overall preweaning mortality of piglets.